Qawaidhul Fiqhiyyah (Sejarah dan Lima Kaidah pokok): Pengertian Kaidah Fiqhiyyah - Mohammad Sofi; Tutik Hamidah (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2024)
It is very important for Muslims to help resolve the legal problems they face every day. If they don't know where to go, they can't know how far something can go or what is more important to do or leave out. In acting or behaving, they are bound by the rules and values ​​they adhere to, which come from religious teachings and good habits. This research is included in the type of normative research. This type of research is a type of research that uses data from library studies, such as books, journals, and other literary sources, as well as previous research findings related to the research topic. Fiqh rules are general rules, cover a number of fiqh issues, and can be known. legal fiqh issues that fall within its scope. This fiqh rule can be used as an independent argument in establishing law, if there is no text argument. The history of the development of qawaidhul Fiqhiyyah is divided into 3 periods starting with the Prophet Muhammad then continued by the companions and tabiin with evidence of the jawamiul kalim hadith. and the existence of these 5 rules as main rules and used as a benchmark in determining fatwas. The 5 rules include: al Umuru bi Maqishidiha, al-Yaqinu La Yuzalu bi Syak, al-Masyaqqoh Tajlibu at-Taysir, ad-Dhororu Yuzalu, al-'Adatu Muhakkamah.